PERLINDUNGAN HUKUM TERHADAP PEMBELIAN TANAH HAK MILIK DENGAN PEMBAYARAN SECARA BERTAHAP YANG DILAKUKAN DI BAWAH TANGAN - margita, Susanto Agata; Kantihka, I Made; -, Nardiman; Widarto, Joko (Gorontalo Law Review, 2024)
The practice of buying and selling plots of land by the community is often found not fully following applicable legal procedures. Seeing these things, it is felt that there is a need to guarantee legal certainty and certainty of rights to land control. Land is a fixed object or object that does not move based on the nature of the object itself. So land cannot be moved - what can be moved is the rights to a plot of land. In this research, the problem is raised, namely whether buying and selling carried out by buyers of freehold land who have good intentions with payments in stages and have fulfilled the legal requirements for buying and selling based on statutory regulations need to receive legal protection and what form of legal protection exists for the purchase of freehold land. carried out privately by means of gradual payments. The research used in this research is Juridical-Normative, namely legal research carried out by examining library materials or secondary materials